2007
DOI: 10.4028/www.scientific.net/kem.347.173
|View full text |Cite
|
Sign up to set email alerts
|

System Fatigue Damage Reliability Assessment of Railway Riveted Bridges

Abstract: According to the fatigue damage failure mechanism of riveted members, a riveted member probabilistic fatigue failure model (RMPFFM) was proposed, and a fracture finite element program is developed to calculate the geometry function of RMPFFM. Furthermore, a system fatigue damage reliability model of riveted bridges was proposed, and based on Monte-Carlo method, a large system fatigue damage reliability analysis program was developed to calculate the system fatigue failure probability. Then the system evaluatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Reliability models have been formulated to quantify the safety, i.e. the trend of the reliability index as function of the number of applied cycles, of both structural details and bridges, see [15,16] among others. An extensive review of the methods employed is reported in [17].…”
Section: Introductionmentioning
confidence: 99%
“…Reliability models have been formulated to quantify the safety, i.e. the trend of the reliability index as function of the number of applied cycles, of both structural details and bridges, see [15,16] among others. An extensive review of the methods employed is reported in [17].…”
Section: Introductionmentioning
confidence: 99%
“…System reliability analysis of riveted bridges and connections has received limited attention, with only a few recent studies in that area. Wang et al (2006Wang et al ( , 2007 developed a system fatigue damage reliability model based on fracture mechanics principles investigating the behaviour of a riveted built-up girder. Probabilistic crack growth analysis of cracks initiating from the holes of angle clips were carried out and combined through systems analysis to estimate the reliability of the riveted girder.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the test data available in the literature, also new fatigue classes were proposed according to their proneness to fatigue failure [14]. Reliability models have been formulated to quantify the safety of both structural details [15] and bridges [16]. An extensive review of the method employed is reported in [17].…”
Section: Introductionmentioning
confidence: 99%